Prevalence Of Oral Soft Tissue Lesions and Risk Behavior in Slum Inhabitants of Bhopal City - Rama S Lodha; Angelin Priya; Manju Toppo; D K Pal; Krishna Murari Lodha (Medsci Publications, 2015)
Background: Oral cavity is prone to changes with advancing age as well as a result of the environmental and life style related factors. Chewing & smoking of tobacco along with consumption of alcohol beverages have become common social habits in India. The objective is to study the prevalence of oral soft tissue lesions & risk behavior in slum study population. Method: A Community based cross-sectional study was done at Bhopal slum area among randomly selected people >15 years of age. All of them interviewed and examination of their oral cavity was done. Results: In this study 476 out of 670 peoples (71%) were addicted. The prevalence of overall oral lesions was 69% (n=462). Tobacco user was most common habit in the study population (48.5 %%), followed by both type habits that is 16.8% and 35.7 % non tobacco substance user. Conclusion; This study reveals high prevalence of oral soft tissue lesions with increased duration of tobacco, non tobacco user and both type habits and emphasis on creating awareness about the misuse of variety of addictive substances in the community. Close follow up and systematic evaluation is required in this group.